'Bring on the dancers': reconceptualising the transition from school to work. Issue 7 (2nd October 2016) - Ashton, Heidi S.; Ashton, David N.
Abstract : Our understanding of the transition from school to work has traditionally been underpinned by a three-stage model. This is one in which the first stage is a preparatory one, where the focus is on school, followed by a second transition stage and ending in a third stage, the successful entry to work. This is a model that has been challenged by work from the 'cultural studies' school but still informs much contemporary work. The study of freelance dancers' entry into work reveals a very different experience of the transition. Rather than a sequence of experiences of school, preparation for work and then entry into established employment, the dancer's experience is one of coterminus experiences of work, vocational training and family life that can start before the entry into primary education. This represents a serious challenge to the three-stage model as a general model for conceptualising transitions. Using the experience of the dancers and building on the work of Becker and Wyn, this paper explores how the concept of belonging points the way forward towards a more comprehensive conceptualisation of the transition.